Assessing the Determinants of Interest Rate Transmission Through Conditional Impulse Response Functions - Saborowski, Christian; Weber, Sebastian (Washington, D.C. : International Monetary Fund, 2013)
We employ a structural panel VAR model with interaction terms to identify determinants of effective transmission from central bank policy rates to retail lending rates in a large country sample. The framework allows deriving country specific pass-through estimates broken down into the contributions of structural country characteristics and policies. The findings suggest that industrial economies tend to enjoy a higher pass-through largely on account of their more flexible exchange rate regimes and their more developed financial systems. The average pass-through in our sample increased from 30 to 60 percent between 2003 and 2008, mainly due to positive risk sentiment, rising inflation and increasingly diversified banking sectors. The crisis reversed this trend partly as banks increased precautionary liquidity holdings, non-performing loans proliferated and inflation moderated.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet